2019
DOI: 10.2174/1570180816666181220121042
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Tyrosyl-DNA Phosphodyesterase 1 (TDP1) Inhibitors Based on the Amines Combining Aromatic/Heteroaromatic and Monoterpenoid Moieties

Abstract: Background: Inhibition of the DNA repair enzyme, tyrosyl-DNA phosphodiesterase 1 (TDP1), may increase the efficacy of cancer drugs that cause damage to tumor cell DNA. Among the known TDP1 inhibitors, there are compounds containing moieties of natural substances, e.g., monoterpenoids. In this work, we synthesized several compounds containing aromatic/ heteroaromatic amines and monoterpenoid groups and assessed their TDP1 inhibition potential. Methods: Structures of all the synthesized compounds were confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Furthermore, derivative 18 had synergistic effect with CPT, 18 increasing CPT cytotoxicity eight-fold in the breast adenocarcinoma MCF-7 cell line [42]. Monoterpene derivatives of substituted anilines were found to be active at low micromolar concentrations (IC 50 = 1.29 µM) for 19 and for 20 (IC 50 = 0.79 µM) ( Figure 2) [43]. Additionally, potent inhibitory activity was found for derivatives containing adamantane.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, derivative 18 had synergistic effect with CPT, 18 increasing CPT cytotoxicity eight-fold in the breast adenocarcinoma MCF-7 cell line [42]. Monoterpene derivatives of substituted anilines were found to be active at low micromolar concentrations (IC 50 = 1.29 µM) for 19 and for 20 (IC 50 = 0.79 µM) ( Figure 2) [43]. Additionally, potent inhibitory activity was found for derivatives containing adamantane.…”
Section: Introductionmentioning
confidence: 96%
“…Monoterpenoid is a useful moiety in potent Tdp1 inhibitors. e.g., the aniline derivative 1 with a myrtenal moiety has inhibitory activity at submicromolar concentrations ( Figure 1 ) [ 16 ]; coumarin-based (-)-myrtenal derivative 2 potentiated the cytotoxicity of camptothecin in cancer cells [ 17 ]; it has also been shown that 3, comprising diazaadamantane and citronellal residues, inhibits Tdp1 with IC 50 (half maximal inhibitory concentration) values of ~15 µM [ 18 ]; geranyl derivative 4 enhances the topotecan antitumor effect in in vitro and in vivo tumor models [ 19 ]; octahydro-2 H -chromene-derived compound 5 was found to be an effective Tdp1 inhibitor with an IC 50 value of 2 µM [ 20 ]. Finally, isobenzofuran 6 , containing a thiophene fragment, has a synergistic effect with topotecan in wild type cells, but not in Tdp1 knockout cells [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these derivatives exhibit analgesic, antiviral, neuroprotective, and antitumor properties [ 14 ]. Moreover, new classes of TDP1 inhibitors with submicromolar half maximal inhibitory concentration (IC 50 ) values have been developed that contain monoterpene moieties; for example, coumarin [ 16 ], 4-arylcoumarin [ 17 ], and adamantane [ 18 , 19 , 20 , 21 ] derivatives as well as octahydro-2 H -chromenes 3 (see Figure 1 ) synthesized from p -menthane monoterpenoid (-)-isopulegol [ 22 ]. Their ability to enhance the Tpc cytotoxic potential was demonstrated for several of these derivatives.…”
Section: Introductionmentioning
confidence: 99%